The use of flexible ureteroscopy is required to improve stone-free rates in ureteroscopy for proximal ureteral stones - Fatih Bıçaklıoğlu; Murat Yavuz Koparal; Ender Cem Bulut (Archive of Urological Research - Peertechz Publications, 2021)
Introduction: The main target in the treatment of proximal ureteral stones (PUS) is to provide a high stone-free rate (SFR) with low morbidity. In this study, we aimed to evaluate the need for flexible ureteroscopy (URS) by retrospectively examining one surgeon's two-year experience of URS for PUS in a center where the flexible ureteroscope and holmium laser lithotriptor are available. Patients and methods: The medical records of all patients who underwent URS due to PUS by a single surgeon from November 2016 to November 2018 were evaluated retrospectively. Success was accepted as patient with no stones or clinically insignificant residual fragments (<4 mm) observed at postoperative 4th and 8th weeks by radiological investigation. Results: URS was performed for PUS in 49 renal units of 48 patients. The mean age was 41.5 ± 12. The operation was completed with pure semirigid URS without the use of flexible URS in 13 (26.5%) RUs. Even in stones with a distance of >5 cm to UPJ, two of nine stones required the use of flexible URS. 34 of 40 stones with a distance of <5 cm to UPJ required the use of flexible URS. 24 of 26 stones with a distance of <3 cm to UPJ required the use of flexible URS. Overall success rates were 100% (38/38) for pure PUS and 93.9% (46/49) for PUS with ipsilateral renal stones. Conclusion: URS is a safe and successful treatment in PUSs. As we have shown in our data, if we want to achieve high SFR with low comorbidity, we should always have flexible URS in the operating room and should use it if necessary.